Error Compensation Method for Pulse Forming Circuit of Power Factor Meter - Zlosnikas, V.; Baškys, A.; Gobis, V. (Elektronika ir Elektrotechnika, 2006)
The error compensation method for power factor meter, witch is suited for case of the linear load has been developed. The block structure of the power factor meter is presented and analyzed. The measurement method in analyzed power factor meter is based on fixing of moments at which signals of current and voltage sensors are crossing zero values. The influence of sensors and pulse forming circuit errors on power factor measurement accuracy was investigated. It has been estimated that the largest influence to accuracy of power factor measurement make errors of pulse forming circuit in current phase measurement channel. The compensation method of error caused by pulse forming circuits offset voltage is proposed. Mathematical basis for this method was developed and class of signals suitable for it was characterized. The power factor measurement algorithm for case of single-phase linear load on basis of proposed method was created. The algorithm is realized on basis of P89C51RD2HBA microcontroller. Ill. 6, bibl. 4 (in Lithuanian; summaries in Lithuanian, Russian and English).